Synthesis, Modification, and Lithium‐Storage Properties of Spinel LiNi0.5Mn1.5O4. Issue 4 (4th January 2021) - Chen, Junxin; Huang, Zhe; Zeng, Weihao; Cao, Fei; Ma, Jingjing; Tian, Weixi; Mu, Shichun
Abstract: Lithium‐ion batteries (LIBs) are currently widely applied in many aspects of life, but with the development, the capacity of lithium‐ion batteries can no longer meet the needs. One of the dominant factors to restricting the capacity of LIBs is the cathode materials. Among the derivatives of spinel cathode LiMn2 O4 (LMO), LiNi0.5 Mn1.5 O4 (LNMO) has become one of the research promising cathode materials in the current LIBs due to its high working voltage (4.7 V) and large theoretical specific capacity (147 mAh g −1 ). However, the short cycle life of LNMO during the electrochemical process limits its large‐scale commercial applications. Thus, it is necessary to summarize and discuss the recent development of LNMO. Through comparison with LiMn2 O4, the structure, electrochemical properties of LNMO, influence of Mn on the performance of LNMO, and the capacity fading mechanism are analyzed and discussed in detail. We also summarize the modification methods of LNMO and the influence of preparation methods on the structure and performance of LNMO. Finally, some prospects of LNMO cathode are put forward. This Review article can provide helpful references for future design and construction of LNMO. Abstract : Under construction : As one of the most potential cobalt‐free cathode materials for lithium‐ion batteries, high‐voltage spinel LiNi0.5 Mn1.5 O4 (LNMO) has been widely investigated. Accordingly, the synthesis/modification methods of LNMO, the influence of Mn on the performance of LNMO, and the mechanism of capacity fading are summarized and analyzed in an attempt to provide references for the design and construction of advanced LNMO materials.